2010
DOI: 10.1111/j.1540-8175.2010.01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography for the Diagnosis of Pulmonary Vein Stenosis after Catheter Ablation of Atrial Fibrillation: A Systematic Review

Abstract: TEE has a high sensitivity and specificity in detecting PV stenosis. Given its wide availability and favorable side effect profile, these data suggest that TEE is very useful tool for the diagnosis of PV stenosis after catheter ablation of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…43; 47 In these settings as well as LTX, computed tomography, magnetic resonance imaging and angiography besides TEE can all be utilized to evaluate for PVO, whether partial or complete. 43–44 Although angiography is a gold standard for the diagnosis and quantification of PVO, its clinical disadvantages include its invasiveness, current inability to perform in an operating room, contrast nephropathy, and the transport of critically ill patients to and from the radiology suite.…”
Section: Commentary: the Perioperative Echocardiographer's Perspectivmentioning
confidence: 99%
See 2 more Smart Citations
“…43; 47 In these settings as well as LTX, computed tomography, magnetic resonance imaging and angiography besides TEE can all be utilized to evaluate for PVO, whether partial or complete. 43–44 Although angiography is a gold standard for the diagnosis and quantification of PVO, its clinical disadvantages include its invasiveness, current inability to perform in an operating room, contrast nephropathy, and the transport of critically ill patients to and from the radiology suite.…”
Section: Commentary: the Perioperative Echocardiographer's Perspectivmentioning
confidence: 99%
“…A recent systematic review of the diagnostic performance of TEE in the detection of PVO (N = 1344: 7 studies) found that TEE, when compared to pulmonary vein angiography, had a sensitivity of (82 –100)% and a specificity of (98 – 100) %. 47 Compared to computed tomography, TEE had a sensitivity of (86 – 100)% and a specificity of 95%. Compared to magnetic resonance imaging, TEE had a sensitivity of 100% with a specificity of (98 –99) %.…”
Section: Commentary: the Perioperative Echocardiographer's Perspectivmentioning
confidence: 99%
See 1 more Smart Citation
“…The late complication of pulmonary vein stenosis is decreasing in frequency due to changing ablation techniques. TOE has a high sensitivity to detect this, 32 but CT and MRI are recommended more often. 33 LA size may decrease with the return of sinus rhythm 34 and therefore should be reassessed as well as LA function using transmitral Doppler or the more sophisticated technique of strain and strain rate.…”
Section: Post-proceduresmentioning
confidence: 99%
“…Moreover, acute changes in PV flow velocities have not been systematically evaluated following PV antrum isolation with GP ablation. Transesophageal echocardiography (TEE) can effectively visualize the PVs and has been shown to have very good sensitivity and specificity for the diagnosis of PV stenosis when compared to other imaging modalities 9 . The aim of this study was to evaluate acute changes in left atrial and PV flow velocities following PV antrum isolation with GP ablation using TEE.…”
mentioning
confidence: 99%